2014
DOI: 10.1080/13527266.2014.894931
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the role of endorser's perceived qualities and consumer characteristics on celebrity endorsement effectiveness

Abstract: This study examines the influence of both endorser's credibility qualities, such as expertise and trustworthiness, and consumers' characteristics, such as gender and team identification, on endorsement effectiveness expressed as purchase intentions. A survey quasi-experimental research design was used in the context of sports celebrity endorsements. Data were collected from 289 respondents via a convenience sample. The findings indicated gender differences only on team identification and not on endorsers' perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 45 publications
3
22
0
2
Order By: Relevance
“…Meanwhile, studies found in Sri Lankan contexts, namely Dissanayake [7] and Dissanayake and Ismail [2] Wanninayake and Dissanayake [28] and Weerasiri and Wanninayake [12] have also used the term "effectiveness of celebrity endorsement" to refer the outcome of the endorsement resulted through managementbased and source-based factors. This is in line with the empirical justifications made by Amos et al [9], Atkin and Block [10], Tzoumaka et al [11]. As per the propositions mentioned by Seno and Lukas [8], perceived effectiveness could be proposed as mechanism of both management-based and source-based factors.…”
Section: Determinant Of the Effectiveness Celebrity Endorsementsupporting
confidence: 69%
See 3 more Smart Citations
“…Meanwhile, studies found in Sri Lankan contexts, namely Dissanayake [7] and Dissanayake and Ismail [2] Wanninayake and Dissanayake [28] and Weerasiri and Wanninayake [12] have also used the term "effectiveness of celebrity endorsement" to refer the outcome of the endorsement resulted through managementbased and source-based factors. This is in line with the empirical justifications made by Amos et al [9], Atkin and Block [10], Tzoumaka et al [11]. As per the propositions mentioned by Seno and Lukas [8], perceived effectiveness could be proposed as mechanism of both management-based and source-based factors.…”
Section: Determinant Of the Effectiveness Celebrity Endorsementsupporting
confidence: 69%
“…Those studies have validated the notion of examining effectiveness of celebrity endorsement towards the endorsed brand as a needful in addressing to research gaps in Sri Lankan context. Meanwhile, Becerra and Badrinarayanan [13], Doss and Carstens [14], Tzoumaka et al [11] and Dissanayake [7] have referred brand-relationship behaviors as a notable concept to be examined with the effectiveness of celebrity endorsement. Further, Aaker [15] referred that brand personality as a concept of brand related property which is perceived to consumers.…”
Section: Research Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Celebrity endorsement has been reported as a significant commercial practice across the world depending on its commercial impact in terms of practice intensity, cost and the strategic effect made on endorsed brands (Ding, Molchanov & Stork ,2010;Dissanayake& Ismail,2015;Elberse & Verleun, 2012;Hung, 2014;Shimp, 2003;Tzoumaka, Tsiotsou, & Siomkos, 2014).The economic impact of celebrity endorsement practices has been justified with media branding contexts (Elberse & Verleun,2012) whilst the nature of celebrity endorsement has been claimed as a fastest growing advertising method as a popular branding strategy across different markets, including China (Hung,Tse & Cheng, 2011). Meanwhile, India is noted an economy that practices wider range of celebrity endorsement strategies for branding (Suprio & Kumar, 2012), and USA is also a significant context in this regard (Plank, 2012).…”
Section: Background Of the Study: Notion Of Effectiveness Of Celebritmentioning
confidence: 99%